The importance of the engine-propeller model accuracy on the performance prediction of a marine propulsion system in the presence of waves. (October 2020) - Saettone, Simone; Tavakoli, Sadi; Taskar, Bhushan; Jensen, Michael Vincent; Pedersen, Eilif; Schramm, Jesper; Steen, Sverre; Andersen, Poul
Abstract: The shipping industry is the heart of international trading activities and the global economy. Maritime transport contributes to environmental pollution through the emission of greenhouse gases. New mandatory regulations aim at improving the environmental performance of ships by encouraging power reduction and alternative fuels. These requirements drew attention to the estimation of the ship performance in the presence of waves considering unconventional combustibles. Investigating the effects of waves on untraditional propulsion plants could help to design more environmentally friendly ships. The purpose of this paper is to determine the importance of the time-varying wake field, ship motions, propeller emergence, and engine response on the performance in waves of a marine propulsion system powered by a medium-speed LNG engine. This is performed by comparing the engine-propeller performance estimated by modelling the propulsion plant at three different levels of complexity. The results illustrated the poor prediction accuracy of the propulsion system performance in waves when the time-varying wake field, ship motions, and propeller emergence are neglected. The influence of the engine response on the performance prediction of the engine-propeller system was negligible. The outcomes of this paper demonstrate the importance of considering the effects of the waves on the propulsion system of a ship during the optimization phase.